RESOURCE MANAGEMENT VARIABLES AS CORRELATE OF COMMUNITY SPORTS DEVELOPMENT AMONG PUBLIC TERTIARY INSTITUTIONS IN KWARA STATE - Ibraheem Musa Oluwatoyin; Ibraheem Tajudeen Olanrewaju; Ambali Abdulrazaq (Universitas Majalengka, 2021)
ABSTRACT. Community sports bind families and communities through shared experienced which also empowers, inspires, and motivates individuals. The purpose of this study was to examine resource management variables including funding, facilities, equipment and sports personnel related to the development of community sports development in public tertiary institutions in Kwara State. Purposive sampling technique was used to select seventy-two (72) respondents in all public tertiary institutions in Kwara State. Self-developed, Structured and validated questionnaire was used with test-retest method of reliability and 0.75r was obtained. Data were analyzed using inferential statistic of PPMC and the findings revealed that three (3) hypotheses tested were significant. This implies that funding, facilities, equipment and sports personnel highly contribute to community sports development. Based on the findings the following conclusion was drawn that resources management variables (funding, facility, equipment and sports personnel) were significantly correlate to community sports development. Based on the conclusion the recommendation was made: that governing council in Public Tertiary Institutions in Kwara State should made sufficient fund, adequate number of sports personnel and provision of standard sports facilities and equipment to Sports Unit (Sports Council) for the development of community sports in tertiary institution in Kwara state.Keywords: Management resources; funding; facilities; sport personnel